Effectiveness of a Developed In-House Breast Phantom in Enhancing the Knowledge of Mammographic Positioning in Radiologic Technology Students: A Quasi-Experimental Study in Thailand - Komany, Kan; Kirisattayakul, Woranan; Ritlumlert, Napat; Tangruangkiat, Sutthirak; Pairodsantikul, Phornpailin; Teankuae, Saiwaroon; kawvised, Supannika (Journal of Health Science and Medical Research, 2024)
Objective: This study aimed to develop an in-house breast phantom, and assess students’ knowledge and satisfaction after using it for mammographic positioning training. Material and Methods: The breast phantom was designed in a half-body shape, and constructed primarily using gelcoat resin, polyurethane foam, and thermoreversible gel. Additionally, silicone type RA-210, known for its high flexibility, tensile strength, elongation at break (620%), and ability to revert to its original shape, was incorporated. This study evaluated the effectiveness of the breast phantom utility in improving students’ knowledge through a nine-item questionnaire; employing a one-group pre-post design. The participants, consisting of 63 Radiologic Technology students, whom rated their satisfaction with the phantom for training purposes using a five-point Likert scale. Results: The mean knowledge score for the breast phantom positioning significantly improved from 5.35±1.61 points (pretest) to 7.32±1.20 points (post-test), following training (p-value<0.001). The students expressed high overall satisfaction with this training aid (4.49±0.58 points). Conclusion: Our breast phantom demonstrates its potential as an effective educational tool that enhances Radiologic Technology students’ understanding of mammographic positioning. However, further research is warranted to develop more advanced phantoms and to explore alternative experimental designs for effective teaching methods.